Nose to Brain Drug Delivery: A Directed Approach for Delivering Drug into Brain (Asian Journal of Pharmaceutics (AJP), 2023)
Poor/delayed bioavailability and hepatic first pass metabolism are the major concern when most common oralroute is chosen for the delivery of drug, which is why alternate therapies are constantly sought for. Oral routeknown to have first dissolution of drugs in stomach followed by absorption in systemic circulation which may leadto delay in the effect of drug and reduce the efficacy and potency of the drug. When it is a matter of targeting tothe brain, less lipophilic drugs have limited accessibility to the brain and thereby delays therapeutic effect. Theselimitations about brain targeting system suggest the requirement for the development of delivery system that willtransport the medication in to the brain with adequate concentration to get pharmacological action. Drug deliveryto brain through nasal mucosa is nowadays emerging way of transport of drug. This method devotes of first passeffect, improves absorption and requires minimal dose. Nasal in situ gel, after administration, converts rapidlyinto gel from liquid after contact with nasal mucosal region allowing adhering of drug in to nasal region. Nasalepithelium allows molecular mass up to 500 Da to pass and thus, the rapid drug accumulation in brain. This reviewfocuses on nasal administration of medicines as a new method of drug transport into the brain. The mechanism ofdrug absorption through the mucous membrane of the nose, different types of nasal drug administration, methodsof production, and polymers required are all described in this paper.